DESIGN OF PEOPLEâS CIRCULATION AND SUPPORTING TRANSPORTATION FACILITIES OF HIGH SPEED RAILWAY STATION USING MICRO SIMULATION MODEL - Hartono, Edwin
High speed railway Jakarta-Bandung project undertaken by PT Kereta Cepat Indonesia China which is an International Joint Venture business entity between China’s consortium as China Railway Engineering Corporation and Indonesian BUMN’s consortium. High speed railway station is a building that serves to move passengers from one mode of transportation to another, with the main mode being the high speed railway. The station is planned to be a connecting station and is planned to be able to serve 2550 passengers / hour. The number of passengers are proportioned based on the choice of mode to be used to plan other transportation facilities. The station building and the high speed railway’s passengers are modelled with PTV Vissim Software. The outputs from this software are performance’s parameters such as density, travel time, and throughput. To improve the station’s performance, 5 ticket counters will be added and 1 arrival and departure gate for each railway. Besides that, the stairs will be changed to escalators for high speed railway’s arrival facility. Building area depends on the number of passengers in each mode during peak hours, and space requirements per person. The transportation facility’s area for bus that is needed during the station's peak hour is 274.5 m2. The required platform area 1305.6 m2. Analysis of the accumulation of vehicles parked on the peak day of the station is done to obtain the number of parking slots needed in the station. The need for this parking slot depends on the number of passengers who use private vehicles and will park their vehicles. The parking slot for motorcycles reaches 235 parking slots, and the car has 204 parking slots.